The Identity of the Herb 'Todda-Vaddi' in Van Rheede's Hortus Malabaricus: The Identity of the Herb ‘Todda–Vaddi’ - Jisha Daniel; Ettickal Sukumaran Santhoshkumar; Madhavan Rajendraprasad; Sabarimuthan William Decruse (Journal of Tropical Life Science, 2021)
The ambiguity on the botanical identity of Todda-vaddi in Rheede's Hortus Malabaricus is clarified as Biophytum reinwardtii (Zucc.) Klotzsch here. A detailed description, photographs and other relevant notes are provided.